2014
DOI: 10.1371/journal.pone.0105693
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging Survival of Corneal Transplantation by Selective Sphingosine-1-Phosphate Receptor 1 Agonist

Abstract: Corneal transplantation is the most used therapy for eye disorders. Although the cornea is somewhat an immune privileged organ, immune rejection is still the major problem that reduces the success rate. Therefore, effective chemical drugs that regulate immunoreactions are needed to improve the outcome of corneal transplantations. Here, a sphingosine-1-phosphate receptor 1 (S1P1) selective agonist was systematically evaluated in mouse allogeneic corneal transplantation and compared with the commonly used immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recently, investigations based on activating PP2A activity pharmacologically in cancer have been highlighted (7). FTY720, also known as fingolimod, is an immunomodulator most widely used in multiple sclerosis and multiple organ transplantation (8)(9)(10). Structurally similar to sphingosine, it is a PP2A activator (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigations based on activating PP2A activity pharmacologically in cancer have been highlighted (7). FTY720, also known as fingolimod, is an immunomodulator most widely used in multiple sclerosis and multiple organ transplantation (8)(9)(10). Structurally similar to sphingosine, it is a PP2A activator (11).…”
Section: Introductionmentioning
confidence: 99%
“…FTY720, a well-documented immunosuppressive agent, is associated with a variety of biological activities, including anti-allograft rejection (Gao et al, 2014;Koch et al, 2016), anticancer (Estrada-Bernal et al, 2012;Lu et al, 2014), anti-inflammation (Aktas et al, 2010;Xu et al, 2014), and antifibrosis (Kramer et al, 2009;Ni et al, 2013). These activities were achieved through the alteration of multiple cell phenotypes, such as viability, proliferation, apoptosis, migration/invasion, and/or epithelial mesenchymal transition, depending on specific disease conditions (Bohler et al, 2009;Lu et al, 2014;Wolf et al, 2009;Zhang et al, 2010;Zhang et al, 2014;Zhang L et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the US Food and Drug Administration approved the use of FTY720 for treatment of multiple sclerosis (Brinkmann et al, 2010). By activating multiple sphingosine-1ephosphate (S1P) receptors (S1PRs), FTY720 effectively inhibits the infiltration of T lymphocytes, prolonging allograft survival (Gao et al, 2014;Koch et al, 2016). FTY720 also induces apoptosis in multiple cancer cell lines (Chen et al, 2014;Estrada-Bernal et al, 2012;Lu et al, 2014;Marvaso et al, 2014;Zhang et al, 2010), showing promise as an anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Recently, fingolimod was also reported to be efficacious in treating autoimmune uveitis and prolonging corneal graft survival. 13,16 In our previous study, we showed that fingolimod inhibits DED-related inflammation in the NOD mouse model. In that study, we observed that the inflammation in ocular surface was greatly ameliorated by fingolimod, and the densities and functions of goblet cells and conjunctival epithelial cells were markedly normalized.…”
mentioning
confidence: 97%
“…Fingolimod is an immunomodulating prodrug; it is used in attenuating multiple sclerosis, prolonging survival of organ allograft, and suppressing autoimmune diseases. [11][12][13] Its mechanism of action is considered to be mediated by the internalization of sphingosine-1-phosphate receptors Copyright 2017 The Authors iovs.arvojournals.org j ISSN: 1552-5783 (S1PRs). 14,15 Recently, fingolimod was also reported to be efficacious in treating autoimmune uveitis and prolonging corneal graft survival.…”
mentioning
confidence: 99%